THE EFFECT OF SOME PRESERVATIVES ON TO BLACK POPLAR Populus nigra L. WOOD WHICH TREATMENT BY SOME DETERIORATION FUNGI IN CHEMICAL PROPERTIES - Z. Tememe; W.J. Kasir (Mesopotamia Journal of Agriculture)
The results showed the effect of preservatives chromate copper boron (CCB), chromated copper arsenate (CCA) and chromated zinc chloride (CZC)on some chemical properties of black poplar wood which treated with wood decay fungi)Neoscytalidium dimidiatum, Alternaria alternata, Acremonium camptosporum) such as ethanol - benzene and hot water soluble extracts, the results showed that both, the preservatives used and incubation period did not effect the above mentioned soluble extracts, while the three kinds of fungi showed a reduction in ethanol - benzene and hot water soluble extracts in the wood infected by them compared to untreated samples of wood. With regard to the effects of preservatives on the amount of lignin, the results revealed that the amount of lignin differed with respect to the incubation periods, it was noticed that, the percentage of lignin increased with increasing periods of incubation of the sample of woods infected by the three kinds of fungi, there was no significant difference among the kind of fungi in their effect on lignin percentages. also, three was no significant variation among the studied preservatives in their effects on lignin.The results also showed a reduction in ash percentage with the increase in incubation periods. for the three kinds of fungi N. dimidiatum caused the highest reduction in ash content compared to the other two fungi (A.alternata and Ac.camptosporum). generally, all preservatives used to protect the wood could maintained the amount of ash in wood without any reduction, their effects did not differ among them significantly. In case of holocellulose , the results indicated that the three kind of fungi caused a reduction in holocellulose percentages and this reduction increased with the increase in the incubation periods, all the studied preservatives showed superiority in keeping the holocellulose at its natural level and there was no significant differences among them in their protection.